TI_GERICHTE 12.2006.143 vom 12. März 2007 , lavoro - licenziamento in tronco - indennità - partecipazione all'utile - TI Tribunale d'appello (2007)
lavoro - licenziamento in tronco - indennità - partecipazione all'utile